(untitled) (Universal International Scientific Journal, 2026)
This article discusses the methodological foundations of the use of digital pedagogical technologies in the process of teaching education. It also analyzes the impact of digital technologies on the effective organization of the educational process, increasing student activity, and their spiritual and moral development.